Comparing Attitudes to Containment Measures of Patients, Health Care Professionals and Next of Kin - Reisch, Thomas; Beeri, Simone; Klein, Georges; Meier, Philipp; Pfeifer, Philippe; Buehler, Etienne; Hotzy, Florian; Jaeger, Matthias (Frontiers in Psychiatry, 2018)
Background: In clinical psychiatric practice, health care professionals (HCP) must decide in exceptional circumstances after the weighing of interests, which, if any, containment measures including coercion are to be used. Here, the risk for patients, staff, and third parties, in addition to therapeutic considerations, factor into the decision. Patients’ preference and the inclusion of relatives in these decisions are important; therefore, an understanding of how patients and next of kin (NOK) experience different coercive measures is crucial for clinical decision making. The aim of this study is to compare how patients, HCP, and NOK assess commonly used coercive measures. Methods: 435 patients, 372 HCP, and 230 NOK rated the Attitudes to Containment Measures Questionnaire (ACMQ). This standardized self-rating questionnaire tested for the degree of acceptance or rejection of 11 coercive measures. Results: In general, HCPs rated the coercive measures as more acceptable than did NOK and patients. The largest discrepancy of the rating was found in regards to the application of coercive intramuscular injection of medication (Effect size: 1.0 HCP vs. patients). However, the ratings by NOK were significantly closer to the patients’ ratings as compared to patients and HCP. The only exception was the acceptance of the treatment in a closed acute psychiatric ward, which was deemed significantly more acceptable by NOK than by patients. Patients who had experienced coercive measures themselves also refused other measures more strongly. Conclusion: Patients particularly rejected intramuscular injections and the authors agree that these should only be used with reservation considering a high threshold. This knowledge about the discrepancy of the ratings should therefore be incorporated into professional training of HCP.